Measures of tolerance and economic prosperity. Issue 1 (11th January 2016) - Gani, Azmat
Abstract : Purpose: – The purpose of this paper is to investigate how a wide range of measures of tolerance, considered from social and institutional perspective relate to growth in the Organization for Economic Cooperation and Development (OECD) countries. Design/methodology/approach: – The empirical framework is based on a growth regression equation with a specification that is common in the growth literature. The estimation includes the generalized least squares, fixed and random effects methods. The empirical analysis is based on cross-country data from a sample of countries from the OECD. Findings: – The findings on social measures of tolerance provide strong support that OECD countries are tolerant toward migrants and women's participation in economic activities and national policy making. The findings also provide evidence that political rights, civil liberties and rule of law as indicators of institutional tolerance, are strongly associated with growth. Practical implications: – The findings presented here from OECD countries lead to the conclusion that tolerance matters for the prosperity of nations. The findings of this study have policy implications beyond the OECD countries and particularly relevant to the developing economies. Originality/value: – This paper makes a new empirical contribution to the tolerance literature.